2020
DOI: 10.1080/23322039.2020.1812258
|View full text |Cite
|
Sign up to set email alerts
|

How does quality of institutions affect the impact of trade openness on economic growth of Ghana?

Abstract: Developing countries, of which Ghana is no exception have actively engaged in trade openness after independence, yet, their economic growth remains low and this calls for urgent attention to address the situation. This study therefore examines the impact of trade openness on economic growth of Ghana for the period 1984-2018 taken into consideration the role quality of institutions play. The results from the autoregressive distributed lag model (ARDL) reveal that, both trade openness and quality of institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
4
21
3
1
Order By: Relevance
“…Interestingly, while the positive coefficient of lnTO is not significant in the long-run, the interaction term lnTO � lnIQ ð Þ has a positive coefficient statistically significant at 5% level. This is different from the condition Duodu et al (2020) identified for Ghana. The statistically significant-combined effect on economic growth for trade openness and institutional quality highlights the importance of building quality institutional frameworks as part of strategies designed to facilitate growth potentials of openness to trade.…”
Section: Long-run and Short-run Estimatescontrasting
confidence: 93%
See 4 more Smart Citations
“…Interestingly, while the positive coefficient of lnTO is not significant in the long-run, the interaction term lnTO � lnIQ ð Þ has a positive coefficient statistically significant at 5% level. This is different from the condition Duodu et al (2020) identified for Ghana. The statistically significant-combined effect on economic growth for trade openness and institutional quality highlights the importance of building quality institutional frameworks as part of strategies designed to facilitate growth potentials of openness to trade.…”
Section: Long-run and Short-run Estimatescontrasting
confidence: 93%
“…This identified variation in estimates is expected given recent changes in the trade environment significantly accommodated in this present study by the extension of the sample period to 2017. In comparison to results from other African economies, Nigeria differs from the case of Cote d'Ivoire documented by Keho and Grace Wang (2017) but similar to the condition Duodu et al (2020) identified for Ghana. The coefficient of labor is positive and statistically significant at the 1% level.…”
Section: Long-run and Short-run Estimatessupporting
confidence: 68%
See 3 more Smart Citations